2017
DOI: 10.1080/10903127.2016.1227001
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Prehospital Medication Dosing Errors: A National Survey of Paramedics

Abstract: This national survey demonstrated a significant number of paramedics are aware of a pediatric dosing error, safety systems specific to pediatric patients are lacking, and that paramedics view pediatric drug cards and eliminating drug calculations as helpful. Pediatric drug-dosing safety in the prehospital environment can be improved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
50
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(52 citation statements)
references
References 21 publications
1
50
0
1
Order By: Relevance
“…First, the response rate to the questionnaire was relatively low; 29%. Previous questionnaire studies showed similar response rates among EMS providers [50][51][52]. As shown by the range in years of experience among the responders, the results are expected to be representative for all EMS providers of both regions.…”
Section: Discussionmentioning
confidence: 53%
“…First, the response rate to the questionnaire was relatively low; 29%. Previous questionnaire studies showed similar response rates among EMS providers [50][51][52]. As shown by the range in years of experience among the responders, the results are expected to be representative for all EMS providers of both regions.…”
Section: Discussionmentioning
confidence: 53%
“…Many critical situations also require the use of drugs or substrates that require a pharmacological intervention to restore vital functions and prevent patients from deteriorating (e.g., anticonvulsive drugs, dextrose, etc.). Although much attention has been paid to in-hospital pediatric emergent medication errors which are present in almost half of all resuscitation cases [12], with significant dose deviation from the prescribed dose reported in up to 16% of the analyzed syringes [35], data regarding EMS-related prehospital medication errors and error prevention strategies are scarce [13]. However, EMS are largely exposed to opportunities for out-of-hospital medication errors, thus severely compromising patient safety.…”
Section: Discussionmentioning
confidence: 99%
“…The latter has been shown to be higher and error-prone when a task is uncommon [45, 47, 48]. Paramedics have little exposure to critically ill children and lack experience to administer emergency medications at pediatric doses [49], with minimal opportunities to gain and maintain competence in this skill [13, 15]. Pediatric situations only account for about 7% of EMS calls [16, 50].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although there were a large number of responses, the overall response rate was low, consistent with most electronic surveys in this population. 21 However, based on the sample size calculation, more than enough responses were received to make estimates with 95% confidence. Further, the geographic distribution of respondents was similar to the distribution of NRPs across the United States.…”
Section: Limitationsmentioning
confidence: 99%